(untitled) (Research, Society and Development, 2023)
Introduction: animal models are essential to evaluate the biocompatibility, tissue response and mechanical function of orthopedic materials used in the treatment of critical size bone defects. Objective: to present a systematic review protocol to identify and summarize the experimental approach for pre-clinical trials of critical size bone defects in large animals. Methods: the protocol was developed based on Preferred for Systematic Review and Meta-Analysis Protocols (PRISMA-P) Guidelines. The bibliographic survey will be carried out in PubMed, Scopus, Embase and Google Scholar databases. Pre-clinical studies in English, Portuguese or Spanish that uses large animal as models of critical size bone defects will be considered. The articles will be analyzed by two reviewers, independently. In case of divergences, the third reviewer will be consulted. The systematic review will be based on Preferred Reporting Items For Systematic Reviews and Meta-Analysis (PRISMA) Guidelines. Final considerations: The proposed systematic review is necessary for the standardization of experimental studies in critical size bone defects.